The commemoration of the dead in medieval times: an exploratory approach based on the case of Coimbra Cathedral - Barbosa Morujão, Maria do Rosário (2025)
This article is an exploratory approach to the study of the commemoration of the dead in the Middle Ages, using the Cathedral of Coimbra and its obituaries as an example. Based on this case, an effort is made to identify the kinds of information that can be obtained from such sources and questions are raised regarding their limitations for reconstructing the ceremonies related to liturgical services for the souls of the dead.  Referências bibliográficasFontesFontes ManuscritasLisboa, Arquivo Nacional da Torre do Tombo, Colegiada de Sta. Cruz do Castelo de Lisboa, m. 1, n. 25. Lisboa, Arquivo Nacional da Torre do Tombo, Cabido da Sé de Coimbra, liv. 4, liv. 5. Lisboa, Arquivo Nacional da Torre do Tombo, Ordem de Cister, Mosteiro de Santa Maria de Celas, mç.13. Lisboa, Arquivo Nacional da Torre do Tombo, Ordem de Cister, Mosteiro de Lorvão, livro 319. Coimbra, Arquivo da Universidade de Coimbra, Cabido e Mitra da Sé de Coimbra, Livro de registos de aniversários, III-D, secção 1ª, estante 5, tabela 3, n. 85, n. 90. Coimbra, Arquivo da Universidade de Coimbra, Cabido e Mitra da Sé de Coimbra, Livro dos aniversários dos capelães da Sé, depósito III-D, secção 1ª, estante 5, tabela 3, n. 84. Coimbra, Arquivo da Universidade de Coimbra, Pergaminhos da Sé de Coimbra, Móv. 7, G. 4, n. 43. Coimbra, Biblioteca Geral da Universidade de Coimbra, Reservados, manuscrito n. 1092. Fontes Impressas CAMPOS, Maria Amélia Álvaro de – A comemoração dos mortos no calendário dos vivos. O obituário medieval da colegiada de São Bartolomeu de Coimbra. Edição crítica e estudo do manuscrito. Coimbra: IUC, 2020. Disponível em https://estudogeral.uc.pt/handle/10316/89491. DAVID, Pierre; SOARES, Torquato de Sousa (eds.) – Liber Anniversariorum Ecclesiae Cathedralis Colimbriensis (Livro das Kalendas). 2 vols. Coimbra: Universidade de Coimbra, 1947-1948. MORUJÃO, Maria do Rosário Barbosa (coord.) – Testamenta Ecclesiae Portugaliae (1071-1325). Lisboa: CEHR-UCP, 2010. PAIVA, José Pedro (coord.) – Portugaliae Monumenta Misericordiarum. Vol. 2: Antes da fundação das misericórdias. Lisboa: União das Misericórdias Portuguesas, 2002. SANTOS, Maria José Azevedo – Um obituário do mosteiro de S. Vicente de Fora. A comemoração dos que passaram deste mundo. Lisboa: Academia Portuguesa da História, 2008. SANTOS, Maria José Azevedo – “Un libro de aniversarios de la colegiata de Santiago de Coímbra. Contribución al estudio del culto del Apóstol en la Edad Media”. Ad Limina. 9 (2018), pp. 185-224. Estudos BAUD, Anne; TARDIEU, Joëlle (dirs.) – Organiser l’espace sacré au Moyen Âge: topographie, architecture et liturgie (Rhône-Alpes - Auvergne). Lyon: Alpara, 2014, p. 98. Disponível em http://books.openedition.org/alpara/3811. CAMPOS, Maria Amélia Álvaro de – “Death commemoration strategies in Medieval Portugal: A mirror of lay participation in religious parochial life (the case of Coimbra)”. Religions. 14: 1443 (2023). Disponível em https://doi.org/10.3390/rel14121443. CAMPOS, Maria Amélia Álvaro de – A comemoração dos mortos no calendário dos vivos. O obituário medieval da colegiada de São Bartolomeu de Coimbra. Edição crítica e estudo do manuscrito. Coimbra: IUC, 2020. Disponível em https://estudogeral.uc.pt/handle/10316/89491. COUTINHO, José Eduardo Reis – “Introdução geral ao Liber Anniversariorum Ecclesiae Cathedralis Colimbriensis (Livro das Kalendas)”. Humanitas. 58 (1998), pp. 419-436. DAVID, Pierre – “Français du Midi dans les évêchés portugais (1279-1390)”. Sep. Bulletin des Études Portugaises, 1943. Lisboa: [s.n.], 1944. ESQUIEU, Yves (dir.) – Viviers, cité épiscopale: études archéologiques. Lyon: Alpara, 1988. Disponível em http://books.openedition.org/alpara/1508. GOMES, Saul António – A solidariedade eclesial na promoção de escolares pobres a estudos universitários. O exemplo coimbrão nos séculos XIV e XV. In Universidade(s): história, memória, perspectivas. Actas do Congresso História da Universidade. 7º Centenário. Vol. 4. Coimbra: Comissão Organizadora do Congresso "História da Universidade", 1991. GOMES, Saul António – “A assinatura do rei D. Dinis: observações para o estudo da chancelaria real portuguesa medieval”. Fragmenta Historica. 7 (2019). Disponível em https://run.unl.pt/handle/10362/117904. LEMAÎTRE, Jean-Loup – “Un livre vivant, l’obituaire”. In GLÉNISSON, Jean (dir.) – Le livre au Moyen Âge. Turnhout: Brepols, 1988. MORUJÃO, Maria do Rosário Barbosa – “La famille d’Ébrard et le clergé de Coïmbra aux XIIIe et XIVe siècles”. In A Igreja e o clero português no contexto europeu. Colóquio Internacional. Lisboa: CEHR, 2005, pp. 77-91. MORUJÃO, Maria do Rosário Barbosa – A Sé de Coimbra: a instituição e a chancelaria (1080-1318). Lisboa: FCG/FCT, 2010. MORUJÃO, Maria do Rosário Barbosa – “Geraldo Peres, cónego da Sé de Coimbra no século XIV”. Revista Portuguesa de História. 31:1 (1996). MORUJÃO, Maria do Rosário Barbosa – Um mosteiro cisterciense feminino: Santa Maria de Celas (séculos XIII a XV). Coimbra: BGUC, 2001. NORTE, Armando – Letrados e cultura letrada em Portugal (sécs. XII e XIII). Vol. 2: Anexos. Lisboa: Faculdade de Letras da Universidade de Lisboa, 2013. Tese de doutoramento. PAIVA, José Pedro (coord.) – Portugaliae Monumenta Misericordiarum. Vol. 2: Antes da fundação das misericórdias. Lisboa: União das Misericórdias Portuguesas, 2002. RODRIGUES, Ana Maria S. A. – “A comemoração dos defuntos nos finais da Idade Média”. In RODRIGUES, Ana Maria S. A.; FERREIRA, Manuel Pedro (coord.) – A catedral de Braga: arte, liturgia e música dos fins do século XI à época tridentina. Lisboa: Arte das Musas / CESEM, 2009, pp. 136-147. SANTOS, Maria José Azevedo – Um obituário do mosteiro de S. Vicente de Fora. A comemoração dos que passaram deste mundo. Lisboa: Academia Portuguesa da História, 2008. SANTOS, Maria José Azevedo – “Un libro de aniversarios de la colegiata de Santiago de Coímbra. Contribución al estúdio del culto del Apóstol en la Edad Media”. Ad Limina. 9 (2018), pp. 185-224. SILVA, André – Físicos e cirurgiões medievais: contextos socioculturais, práticas e transmissão de conhecimentos (1192-1340). Porto: CITCEM, 2016. TABBAGH, Vincent – “Une lecture des obituaires de quelques cathédrales de France septentrionale, XIIe-XVe siècle”. Le Moyen Âge. 124 (2018), pp. 553-580.